Detection of errors in the Indonesian standard mushaf based on pixels to support accelerated verification - Widyaningsih, Tri Wahyu; Madenda, Sarifuddin; Salim, Ravi Ahmad; Nugraha, Nurma (International Journal of Advances in Intelligent Informatics, 2025)
One effort to maintain the validity of the Al-Qur'an manuscript is the analysis and verification of the manuscript by experts (Pentashih). Currently, manuscript verification without translation takes 30 working days. Therefore, to support Pentashih in reviewing the manuscript, technology is needed to expedite the Pentashih process and prevent analysis errors caused by Pentashih fatigue. This study conducts a writing analysis of the target manuscript by referring to the template manuscript, implementing image preprocessing stages, applying SSIM for analysis, and employing the pixel-matching method. This method examines the manuscript's writing by comparing two block images at the pixel level. Block images are produced by preprocessing the manuscript images before image-matching analysis is performed. Image preprocessing comprises: cropping the outer frame, cropping the inner frame, segmenting the page into row images, adjusting margins, aligning image sizes, segmenting rows into block images, and aligning positions between block images. Pixel value differences are calculated at the same positions across each column and row of the template and target block images. Block image positions with pixel values ≥ 200 occur in 5 consecutive columns, adjacent rows with a distance = 1, and an SSIM value ≥ 0.9, both images meet the mismatch criteria. These findings indicate that the proposed approach provides an efficient and accurate solution for automating the verification of the Indonesian Standard Mushaf.